FAKTOR-FAKTOR PEMENGARUH KUNJUNGAN WISATAWAN DALAM RUANG LINGKUP DOMESTIK - Rah Adi Fahmi Ginanjar; Desi Lafani (Jurnal Riset Ilmu Ekonomi, 2021)
In order to complete this research, this article is explained about the amounts of domestic tourists who is arrived into a region and also between any regions in Indonesia. Through the time series data method as well as the concept of error correction model (ECM), even in the short term, long term, or equilibrium at each timeline, the number of these variables have been tested. Based on the results of short-term tests, lots of information could be categorized as the few factors which is affected the amounts of domestic tourist arrival into a region, such as national income, quality of education, and also the lifestyle. Besides, lots of thing that could be categorized as the few factors which is affected the amounts of domestic tourist arrival between few regions are about the exchange variable and inflation rate. But if we talked about the results of long-term test which still about the amounts of domestic tourists between few regions, the affected factor is only about national income without anything related to other problems such as quality of education or lifestyle as well. As an addition, the analysis of ECT concept also gave some results about an equilibrium per each period of domestic tourist arrival into a region and also between few regions, it was at 1,23% and 0,95%. Furthermore, on the long-term equilibrium, there was no balance at all, both in cases of tourist arrival into a region and between regions.